1999
DOI: 10.1111/j.1439-0531.1999.tb01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Secretion and Management of Parturition in the Pig

Abstract: This paper will examine the augmentation of oxytocin (OT) secretion in the final day before parturition in the pig, and review the key endocrine systems of influence. Recent experiments have shown that increases in plasma OT above baseline secretion were not seen until 7 hours prior to the birth of the first piglet. Progesterone release begins to decline some days before birth and is unlikely to provide such acute control of OT release immediately before birth. The involvement of relaxin is complex but it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…When this occurs, the piglets will be pushed against a closed cervix, which is clearly not desirable. When PG is used, the time of complete relaxation of the cervix (= the time when OT may be used) is not exactly known, and may differ between sows (Gilbert, 1999). Median of farrowing duration (184 minutes), birth interval (14 minutes) and percentage stillborn piglets (5.6 per cent) were lower compared to literature data (Oliviero and others 2009, De Pasille and Rushen, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…When this occurs, the piglets will be pushed against a closed cervix, which is clearly not desirable. When PG is used, the time of complete relaxation of the cervix (= the time when OT may be used) is not exactly known, and may differ between sows (Gilbert, 1999). Median of farrowing duration (184 minutes), birth interval (14 minutes) and percentage stillborn piglets (5.6 per cent) were lower compared to literature data (Oliviero and others 2009, De Pasille and Rushen, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed no negative effects of oxytocin (10 -30IU) on these parameters (Kirkwood et al, 1998;Wehrend et al, 2005;Kaeoket et al, 2006). This may by explained by differences in time needed for a full relaxation of the cervix after the induction with prostaglandins (Gilbert et al, 1999). The administration of high doses of oxytocin may induce hard pressure upon the piglets and their umbilical cord, which leads to hypoxia (Mota-Rojas et al, 2005).…”
Section: The Use Of Oxytocin In Combination With Prostaglandinmentioning
confidence: 91%
“…In this way, the piglets will be pushed against a closed cervix, which is clearly not desirable. When prostaglandins are used, the time of complete relaxation of the cervix (= the time when oxytocin may be used) is not exactly known and may differ between sows (Gilbert et al, 1999). Some authors concluded that oxytocin (10 -30IU) increases the percentage of stillborn piglets (Yang et al, 1996;Alexopoulos et al, 1998;Cassar et al, 2005).…”
Section: The Use Of Oxytocin In Combination With Prostaglandinmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiment 2, we studied the behaviour of indomethacin-treated, non-pregnant, nonnest building female pigs to examine the specificity of the changes to nest building observed in experiment 1. Preliminary data from experiment 1 on OT secretion immediately before birth have been reported elsewhere (Gilbert 1999).…”
Section: Introductionmentioning
confidence: 99%